2023
DOI: 10.5851/kosfa.2023.e44
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Consumption of Animal Products on the Gut Microbiome Composition and Gut Health

Abstract: The gut microbiome is critical in human health, and various dietary factors influence its composition and function. Among these factors, animal products, such as meat, dairy, and eggs, represent crucial sources of essential nutrients for the gut microbiome. However, the correlation and characteristics of livestock consumption with the gut microbiome remain poorly understood. This review aimed to delineate the distinct effects of meat, dairy, and egg products on gut microbiome composition and function. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…The implications of this study go beyond just those of food decision making with HE, as SCFA such as butyrate is shown to maintain gut integrity and is protective against HE ( 39 ). Other studies have shown an association of high meat consumption with a decrease in SCFA producing gut bacteria such as Lachnospiraceae and Ruminococcaceae ( 40 ).…”
Section: Discussionmentioning
confidence: 96%
“…The implications of this study go beyond just those of food decision making with HE, as SCFA such as butyrate is shown to maintain gut integrity and is protective against HE ( 39 ). Other studies have shown an association of high meat consumption with a decrease in SCFA producing gut bacteria such as Lachnospiraceae and Ruminococcaceae ( 40 ).…”
Section: Discussionmentioning
confidence: 96%
“…The intestinal microbiota has long been recognized for its importance, particularly in the realm of veterinary medicine. These microorganisms colonize various anatomical sites of the animal host other than GI, such as the skin, mucosal surfaces (respiratory tract, urogenital tract), and internal organs, forming complex microbial communities known as microbiomes [2]. Early-life microbial succession in the gut of animals refers to the dynamic process by which diverse microbial communities, primarily bacteria, establish themselves in the gut of a newborn.…”
mentioning
confidence: 99%